Biomass distribution in components of Pinus patula in reforestations in the Sierra Norte of Oaxaca, Mexico - Pacheco Aquino, Guadalupe; Manzano-Méndez, Filemón; Martínez-López, Joel (BOSQUE, 2024)
A system of allometric equations was generated and evaluated to estimate the total biomass and its components during the reforestation of Pinus patula in Sierra Norte of Oaxaca State, Mexico. For this purpose, 18 trees were directly sampled, which represented the growth potential of the site. Using this destructive method, the fresh weight in situ, and samples of each component of the tree were obtained to estimate the dry weight. The total tree biomass was related to its normal diameter by adjusting allometric equations using regression techniques. The exponential equation was selected to estimate the total biomass because it presented the best statistical indicators. The exponential model was again fitted to each component by using a system of simultaneous equations. The allometric equations obtained showed good performance in estimating aerial biomass in components and total tree biomass in the reforestation of Pinus patula, with similar diameters and environmental conditions. The distribution of aerial biomass estimated in the field was 69.8 % for stems, 20.5 % for branches, and 9.7 % for foliage.